Single Nucleotide Variants as Proxies for HLA-A*31:01 in Native American Populations - Fernandes, Vanessa Câmara; Pretti, Marco Antônio M.; Tsuneto, Luiza Tamie; Petzl-Erler, Maria Luiza; Suarez-Kurtz, Guilherme (Frontiers in Pharmacology, 2022)
Carbamazepine triggers dermatologic hypersensitivity reactions, linked to specific human leukocyte antigens (HLAs), especially HLA-B*15:02 and HLA-A*31:01. Previous efforts to identify single nucleotide variants (SNVs) with high predictive value as HLA proxies, revealed that rs1061235 and rs17179220 fulfill these requirements for HLA-A*31:01 in some but not all populations. Herein we explored the predictive performance of rs1061235 and rs17179220 as HLA-A*31:01 tags in individuals of Native American ancestry, that are largely underrepresented in pharmacogenomic studies. The study cohorts comprised the overall Admixed American superpopulation of the 1000 Genomes Project (1KG_AMR), a subcohort of individuals with predominant Native ancestry (1KG_NAT), the Native American population of the Human Genome Diversity Project (HGDP), and Kaingang (KRC) and Guarani (GRC and GKW) adults from indigenous reservation areas in Brazil. The diversity of cohorts is reflected in the range of frequencies of HLA-A*31:01 (range 0.02 - 0.65), rs1061235 (0.03 - 0.13) and rs17179220 (0.12 - 0.66), the extent of linkage disequilibrium between HLA-A*31:01 and each SNV and the predictive performance of these SNVs as HLA-A*31:01 proxies. NPV (negative predictive value), the metric of primary interest for pharmacogenetic-informed carbamazepine prescription was perfect (NPV = 1.0) for both SNVs in 1KG_AMR and 1KG_NAT, for rs17179220, but not for rs1061235 (NPV = 0.91) in HDGP, and for rs17179220 in GWK, but not GRC (NPV = 0.88) or KRC (NPV = 0.80). Collectively, the data support the notion that rs1061235 and rs17179220 are not optimal proxies for HLA-A*31:01 across populations of Native American ancestry.